A monoclonal antibody to O-acetyl-GD2 ganglioside and not to GD2 shows potent anti-tumor activity without peripheral nervous system cross-reactivity. - Nidia Alvarez-Rueda (Public Library of Science (PLoS), 2011)
Background Monoclonal antibodies (mAb) against GD2 ganglioside have been shown to be effective for the treatment of neuroblastoma. Beneficial actions are, however, associated with generalized pain due to the binding of anti- GD2 mAbs to peripheral nerve fibers followed by complement activation. Neuroblastoma cells that express GD2 also express its O-acetyl derivative, O-acetyl- GD2 ganglioside (OAcGD2). Hence, we investigated the distribution of OAcGD2 in human tissues using mAb 8B6 to study the cross-reactivity of mAb 8B6 with human tissues. Methodology/principal findings The distribution of OAcGD2 was performed in normal and malignant tissues using an immunoperoxydase technique. Anti-tumor properties of mAb 8B6 were studied in vitro and in vivo in a transplanted tumor model in mice. We found that OAcGD2 is not expressed by peripheral nerve fibers. Furthermore, we demonstrated that mAb 8B6 was very effective in the in vitro and in vivo suppression of the growth of tumor cells. Importantly, mAb 8B6 anti-tumor efficacy was comparable to that of mAb 14G2a specific to GD2. Conclusion/significance Development of therapeutic antibodies specific to OAcGD2 may offer treatment options with reduced adverse side effects, thereby allowing dose escalation of antibodies.